2023
DOI: 10.1097/pas.0000000000002046
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Tumor Resembling Ovarian Sex Cord Tumors: 23 Cases Indicating Molecular Heterogeneity With Variable Biological Behavior

Abstract: Uterine tumor resembling ovarian sex cord tumor (UTROSCT) is a rare mesenchymal neoplasm that mainly harbors NCOA1-3 rearrangements with partner genes ESR1 or GREB1. Here, we explored 23 UTROSCTs by targeted RNA sequencing. The association between molecular diversity and clinicopathologic features was investigated. The mean age of our cohort was 43 years (23–65 y). Only 15 patients (65%) were originally diagnosed with UTROSCTs. Mitotic figures ranged from 1 to 7/10 high power fields, of primary tumors and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…On the other hand, recent findings have identified recurrent fusions involving NCOA2 and NCOA3 (such as ESR1-NCOA3, ESR1-NCOA2, or GREB1-NCOA2) in UTROSCT. These genes, NCOA2 and NCOA3, are known to be involved in steroid hormone regulation, and the disruptions in their nuclear receptor coactivator domains are thought to play a crucial role in the development of UTROSCT [7,76,104,105,124,125,[131][132][133][134].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, recent findings have identified recurrent fusions involving NCOA2 and NCOA3 (such as ESR1-NCOA3, ESR1-NCOA2, or GREB1-NCOA2) in UTROSCT. These genes, NCOA2 and NCOA3, are known to be involved in steroid hormone regulation, and the disruptions in their nuclear receptor coactivator domains are thought to play a crucial role in the development of UTROSCT [7,76,104,105,124,125,[131][132][133][134].…”
Section: Discussionmentioning
confidence: 99%
“…Bi et al reported that in recurrent UTROSCT cases, the GREB1::NCOA2 fusion was the most common, accounting for 57% of cases, with GREB1::NCOA1 and ESR1 fusions also detected. These GREB1-rearranged tumors were typically more advanced, larger, and occurred in older patients [132]. Lu et al reported recurrent NCOA1-3 rearrangements in 87.5% (14/16) of their series, without JAZF1, PHF1, BCOR, or YWHAE rearrangements, underscoring the diagnostic value of these rearrangements in distinguishing UTROSCT from endometrial stromal tumors [131].…”
Section: Gene Fusions In Utrosctmentioning
confidence: 95%
See 2 more Smart Citations
“…Expression of CD56, WT1, SF-1, and CD99 was detected in a high percentage of analyzed samples, and diffused expression of ER and PR was detected in all cases. Although there was a high molecular variability amongst samples, 5 different types of gene fusions were detected, all containing NCoA fusion partners with GREB1-NCoA2 fusions being the most common ( 102 , 103 ). A recent study found that malignant UTROSCT is more likely to have higher mitotic activity, high expression of stromal PD-L1, and a gene alteration involving NCoA2 ( 104 ).…”
Section: Oncogenic Gene Fusions With Ncoa As a Gene Partnermentioning
confidence: 99%